Learning to write chinese characters among non-native chinese learners / Ting Hie-Ling...[et al.] - Ling, Ting Hie; Chin, Ch'ng Looi; Unin, Norseha (2019)
Learning to write Chinese characters is often challenging for non-native Chinese learners mainly because the writing system is completely different from the alphabetical system. Traditionally, rote learning is commonly used in the teaching and learning of Chinese characters but it is often considered as laborious. Studies indicate mobile applications (MAs) can facilitate the learning process better (Shinagawa, 2012; Wong et al, 2010) especially for non-native Chinese learners. This study is designed to compare the use of both learning methods to promote the correct order of writing Chinese characters. A hundred Level 2 Mandarin undergraduates participated in this study. They were given a Pre-Test before they were divided equally into Treatment group (TG) and Control group (CG). The CG used traditional method of rote learning to practice writing, while TG used three differrent MAs to practice for three weeks. Later, all of them were required to complete a Post-Test. The scores for pre-test and post-test were analyzed and compared. The results suggest that traditional and MA method give significant and positive impacts on the improvement of writing order. Futher studies are needed to seek participants' preferences in learning writing order as a way to cater for their personal needs in writing Chinese characters.